Avaliação das ações de rastreamento do câncer de colo uterino no Parque Indígena do Xingu - Scopin, Ana Carolina Carvalho [UNIFESP] (2019)
Introduction: There are few epidemiological studies on Human Papillomavirus (HPV) infection and cervical cancer in indigenous populations. Because it is a specific population with habits and rituals of its own, HPV infection and its onco genesis could not present the same evolution in Relation to the populations commonly studied. Through the data over time analysis, it was possible to determine the most appropriate form of follow-up, aiming the diagnosis of cervical lesions, reduction of care costs and lower morbidity. Objective: To evaluate 13 years of cervical cancer screening actions and assistance in the Xingu Indigenous Park, through cytological alterations analysis, correlating age and DNA-HPV test. Methods: This is an observational, transversal and retrospective study conducted by data analysis of screening and control actions of uterine cervical cancer in the scope of the Xingu project of the Universidade Federal de São Paulo (UNIFESP). The population studied consiste do find igenous, sexually active women, aged 11 years or older, belonging to sixteen ethnic groups residing in the middle, lower and east Xingu regions. The study was developed with the analysis of the result sobtained by convencional cervical screening test (Pap smear). Results: The population coverage of cytological examination in the period averaged 89.4%. In all actions, there was a higher percentage of normal cytological results. In 2005 and 2010 years, occurred the largest number of cytological alterations, with high-grade squamous intra epithelial lesion (HSIL) and low-grade squamous intraepithelial lesion (LSIL) respectively. Only 3 cases of cervical cancer were documented over the 13 years of follow-up. The HPV positivite rate was 24.5% and latency 22.9%. Conclusion: It was observed that the high coverage of the population was valuable in maintaining the quality of screening because of the large number of normal exams and rare cases of cancer compared to the national incidence. The extremes of the ages showed a higher percentage of LSIL and HSIL respectively. The basic DNA-HPV test, without genotyping, confirmed a higher percentage of positivity in those who had HSIL.